A Possible Chemical Clock in High-mass Star-forming Regions: N(HC3N)/N(N2H+)? - Y. X. Wang; J. S. Zhang; H. Z. Yu; Y. Wang; Y. T. Yan; J. L. Chen; J. Y. Zhao; Y. P. Zou (The Astrophysical Journal Supplement Series, 2023)
We conducted observations of multiple HC _3 N ( J = 10−9, 12−11, and 16−15) lines and the N _2 H ^+ ( J = 1−0) line toward a large sample of 61 ultracompact (UC) H ii regions, through the Institut de Radioastronomie Millmétrique 30 m and the Arizona Radio Observatory 12 m telescopes. The N _2 H ^+ J = 1−0 line is detected in 60 sources and HC _3 N is detected in 59 sources, including 40 sources with three lines, 9 sources with two lines, and 10 sources with one line. Using the rotational diagram, the rotational temperature and column density of HC _3 N were estimated toward sources with at least two HC _3 N lines. For 10 sources with only one HC _3 N line, their parameters were estimated, taking one average value of T _rot . For N _2 H ^+ , we estimated the optical depth of the N _2 H ^+ J = 1−0 line, based on the line intensity ratio of its hyperfine structure lines. Then the excitation temperature and column density were calculated. When combining our results in UC H ii regions and previous observation results on high-mass starless cores, the N (HC _3 N)/ N (N _2 H ^+ ) ratio clearly increases from the region stage. This means that the abundance ratio changes with the evolution of high-mass star-forming regions (HMSFRs). Moreover, positive correlations between the ratio and other evolutionary indicators (dust temperature, bolometric luminosity, and luminosity-to-mass ratio) are found. Thus we propose the ratio of N (HC _3 N)/ N (N _2 H ^+ ) as a reliable chemical clock of HMSFRs.